1991
DOI: 10.1172/jci115241
|View full text |Cite
|
Sign up to set email alerts
|

L-type cardiac calcium channels in doxorubicin cardiomyopathy in rats morphological, biochemical, and functional correlations.

Abstract: Doxorubicin (DXR) is an effective antitumor agent in a wide spectrum of neoplasms. Chronic treatment is associated with cardiomyopathy and characteristic myocardial ultrastructural changes, which include swelling of the t tubules. Accordingly, we investigated excitation-contraction coupling in cardiomyopathic rat heart resulting from chronic DXR treatment. Using the whole-cell patch clamp technique, we studied the L-type calcium channel in single cells enzymatically isolated from normal (CTRL) and DXR rat hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 37 publications
1
45
1
Order By: Relevance
“…Statistical significance was set at P<0.05. (Keung et al, 1991). Therefore, effect of a L-type Ca 2+ channel blocker, nifedipine, on DOX-induced Ca 2+ signal was examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical significance was set at P<0.05. (Keung et al, 1991). Therefore, effect of a L-type Ca 2+ channel blocker, nifedipine, on DOX-induced Ca 2+ signal was examined.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the molecular basis of DOX-induced intracellular Ca 2+ regulation has been examined (Keung et al, 1991), inhibits Na + -Ca 2+ exchanger (Caroni et al, 1981), or releases Ca 2+ from SR (Zorzato et al, 1985;Kim et al, 1989). Our results have shown that DOX-mediated increase of [Ca 2+ ]i is due to a release of Ca 2+ from SR through ROS-mediated opening of RyR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] However, the present study showed that myocardial alterations in DOX-induced cardiotoxicity were less prominent than those in previous reports. We used a rat model in DOX-induced cardiomyopathy according to the method of Keung et al 22 with some modification. However, the sex of rats, the route and span of drug administration, and the duration until sacrifice after final drug administration were different from previous papers.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation was performed in accordance with the Guide for the Care and use of Laboratory Animals published by the US National Institutes of Health (NIH publication No 85-23, revised 1985). DOX-induced cardiomyopathy was induced as previously described by Keung et al 22 with some modifications. DOX was administered ip at a dose of 2.5 mg/kg once a week for 10 weeks.…”
Section: Dox-induced Cardiomyopathy Modelmentioning
confidence: 99%